2019
DOI: 10.12963/csd.18531
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Serious Games and Stakeholders’ Needs for Vocal Training Game Development

Abstract: Objectives:The present study intended to identify the needs and development directions of a serious vocal training game for better motivation and commitment of patients with voice disorder to voice therapy. Methods: A literature review, a survey of stakeholders' needs, and a benchmarking analysis of three vocal training games (Visi Pitch, Dr. Speech, and Vox System) was conducted. Results: From the literature review, thirteen game user experience scales (usability, narratives, play engrossment, enjoyment, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…While the games scored well in useability, personal gratification, and enjoyment, the researchers noted that therapists found the visuals outdated. Furthermore, therapists wanted the game graphics and narratives to be more age-appropriate and engaging (Yang et al, 2019).…”
Section: Serious Games and Media For Pediatric Voice Therapymentioning
confidence: 99%
“…While the games scored well in useability, personal gratification, and enjoyment, the researchers noted that therapists found the visuals outdated. Furthermore, therapists wanted the game graphics and narratives to be more age-appropriate and engaging (Yang et al, 2019).…”
Section: Serious Games and Media For Pediatric Voice Therapymentioning
confidence: 99%
“…A 2019 study that analyzed the needs and development of serious vocal training games concluded that, when looking at three existing vocal therapy games, clinicians were relatively unsatisfied with many aspects of the game, including creative freedom, therapy continuity and customization. They suggested the games could be improved by providing "different scenarios, stories, difficulty levels, and modern graphic designs to maintain patients' motivation, fun, and commitment for better effectiveness of voice therapy games" (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%